DEVELOPMENT OF INTERACTIVE LEARNING MEDIA ASSISTED BY SMART APPS CREATOR 3 IN SPLDV MATERIALS TO INCREASE STUDENTS' LEARNING INTEREST - Andi Dian Angriani; A. Karmila Kahar; Nurul Aini Fitrah Prastika; Ahmar Zaky Yamani Yaser Arafah; A. Tenri Megga Sompa (Universitas Muhammadiyah Lampung, 2025)
Technological advances require innovation in the learning process that is in line with the characteristics of today's students. This study aims to develop an interactive learning media based on Smart Apps Creator 3 (SAC) on the Two-Variable Linear Equation System (SPLDV) material to increase the learning interest of grade VIII junior high school students. This research uses the Research and Development (R&D) method with a 4D development model that includes the stages of Define, Design, Develop, and Disseminate. The subject of the trial was a grade VIII student of State Junior High School 3 Sungguminasa. The results of validation by experts show a validity rate of 90% (very valid category). Practicality assessments from teachers and students show that media is easy to use and engaging, while the effectiveness of media is reflected in students' increased interest in learning during learning. This media has proven to be able to present SPLDV material visually and interactively so as to create a more meaningful learning experience. Therefore, this medium is recommended to be applied more widely in mathematics learning. Further research is suggested to examine the influence of media on learning outcomes and critical thinking skills, as well as to expand implementation to other mathematics materials and various levels of education.